PENDIDIKAN KESEHATAN TENTANG PEMANFAATAN DAUN KELOR SEBAGAI UPAYA MENCEGAH ANEMIA PADA IBU HAMIL - Dian Soekmawaty; Irni Setyawati; Kusniyati Utami; Hardaniyati (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
The pregnancy period is a period that really determines the quality of human resources in the future because a child's growth and development is determined from the time the fetus is in the womb. Pregnant women are one of the groups most vulnerable to nutritional problems such as chronic energy deficiency (CED) and anemia. The World Health Organization (WHO) reports that 56% of pregnant women in developing countries suffer from anemia. One of the complementary therapies is using Moringa leaves to prevent anemia in pregnant women. The aim of this community service activity is to increase mothers' understanding of the use of Moringa leaves as an effort to prevent anemia. in pregnant women. The method used in this community service stage consists of 3 stages, namely pretest, then Health Education about the use of Moringa leaves to prevent anemia, then followed by a post-test process to determine the level of knowledge of pregnant women. Results: The posttest results showed an increase in knowledge, with 23 (76.6%) pregnant women having good knowledge and 23.3% of pregnant women having sufficient knowledge about nutrition for pregnant women. Conclusion: The outreach activities carried out are expected to make mothers- Mothers understand more about Moringa leaves to prevent anemia in pregnant women. The material provided is knowledge about anemia in pregnant women and is presented in a straightforward and clear manner. The community becomes enthusiastic in participating in outreach activities, considering the large benefits that can be derived from community service activities